Histopathology Of Endometrial Uterine Bleeding Postmenopausal- National Maternal Perinatal Institute - Ayala-Peralta, Félix (2019)
Objective. Determine the prevalence of endometrial histology in patients with postmenopausal uterine bleeding. Materials and methods. Observational, retrospective, cross. Study 40 cases had histopathological study of patients who had uterine bleeding whose ages were 50 or more years of age were included. Pathological findings were reviewed.